Obstetric outcome in pregnancy with thrombophilia: a comparative study of two different thromboprophylaxis regimes - Asthana, Shilpa; Sodhi, Bandana; Kumar, Satish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thrombophilia in pregnancy is a leading cause of both maternal and fetal mortality and morbidity. Thromboprophylaxis is administered to the patients with thrombophilia with an aim to improve the obstetric outcome. Although various studies have proven the benefits of treating pregnant women with thrombophilia, few studies comparing the usage of Unfractionated Heparin (UFH) and Low Molecular Weight Heparin (LMWH) along with low - dose ecosprin in terms of obstetric outcome, incidence of IUGR, pre-eclampsia, mode of delivery, neonatal birth weight and adverse effects of therapy have been published. This study was undertaken to compare two different treatment modalities using either UFH or LMWH (along with low dose ecosprin) in pregnant patients with thrombophilia with respect to obstetric outcomes and incidence of adverse effects of therapy. Methods: This randomised, prospective study was conducted in patients with a previous history of recurrent pregnancy losses or previous adverse pregnancy outcomes. Sixty patients diagnosed with thrombophilia were randomly divided into two groups of 30 patients each (Group I and II). Patients in Group I received Inj Unfractionated Heparin 5000 I.U. (s.c) twice daily and Tab Ecosprin 75 mg once daily and those in Group II received Inj LMWH (enoxaparin) 40 mg (s.c) once daily and Tab Ecosprin 75 mg once daily. These pregnancies were followed and the obstetrical outcome was determined. The data collected was analysed using the Student’s `t`test and Chi-square test. P values < 0.05 were considered statistically significant. Results: There was no significant difference observed between two treatment groups with respect to pregnancy outcomes, incidence of IUGR, pre-eclampsia and mode of delivery (vaginal or by caesarean section). Treatment with a combination of LMWH and ecosprin administered to patients in Group II resulted in significantly higher neonatal birth weights. Conclusions: Treatment with a combination of LMWH and ecosprin resulted in significantly higher neonatal birth weights as compared to a regime that comprised of UFH and ecosprin. There was no significant difference seen in patients who were treated with either UFH or LMWH along with low dose ecosprin in terms of obstetric outcome, incidence of IUGR, pre-eclampsia and mode of delivery. No thromboembolic events or side effects were witnessed in patients subjected to either of the two regimes using LMWH or UFH with low dose ecosprin, thus, highlighting the safety of the antithrombotic therapy during pregnancy as used in this study.